Alpha-1 Antitrypsin Reduces Severity of Pseudomonas Pneumonia in Mice and Inhibits Epithelial Barrier Disruption and Pseudomonas Invasion of Respiratory Epithelial Cells - Pott, Gregory; Beard, Scott; Bryan, Courtney; Merrick, Daniel; Shapiro, Leland (Frontiers in Public Health, 2013)
Nosocomial pneumonia (NP) is the third most common hospital-acquired infection and the leading cause of death due to hospital-acquired infection in the US. During pneumonia and non-pneumonia severe illness, respiratory tract secretions become enriched with the serine protease neutrophil elastase (NE). Several NE activities promote onset and severity of NP. NE in the airways causes proteolytic tissue damage, augments inflammation, may promote invasion of respiratory epithelium by bacteria, and disrupts respiratory epithelial barrier function. These NE activities culminate in enhanced bacterial replication, impaired gas exchange, fluid intrusion into the airways, and loss of bacterial containment that can result in bacteremia. Therefore, neutralizing NE activity may reduce the frequency and severity of NP. We evaluated human alpha-1 antitrypsin (AAT), the prototype endogenous NE inhibitor, as a suppressor of bacterial pneumonia and pneumonia-related pathogenesis. In AAT+/+ transgenic mice that express human AAT in lungs, mortality due to Pseudomonas aeruginosa (P.aer) pneumonia was reduced 90% compared to non-transgenic control animals. Exogenous human AAT given to non-transgenic mice also significantly reduced P.aer pneumonia mortality. P.aer-infected AAT+/+ mice demonstrated reduced lung tissue damage, decreased bacterial concentrations in lungs and blood, and diminished circulating cytokine concentrations compared to infected non-transgenic mice. In vitro, AAT suppressed P.aer internalization into respiratory epithelial cells and inhibited NE or P.aer-induced disruption of epithelial cell barrier function. The beneficial effects of human AAT in murine P.aer pneumonia raise the possibility of AAT use as a prophylactic treatment for NP in humans, and suggest a role for AAT as an innate immune mediator.